A cross-sectional study on the knowledge, attitude, and practice of pregnant women regarding medication use and restriction during pregnancy. - Ogechi C. Obi; Chibueze Anosike (Elsevier, 2023)
Background: The use of medication during pregnancy is a complex issue that requires careful consideration to avoid potential harm to the developing fetus. Despite the existence of guidelines and restrictions on medication use during pregnancy, pregnant women in Nigeria often have limited access to information regarding drug use and may rely on their own judgment or the advice of non-professionals when making decisions about medication use. Objectives: To assess Nigerian pregnant women's knowledge, attitude, and practice toward the use of drugs and restriction/contraindications in pregnancy. Methods: A descriptive cross-sectional study was conducted among pregnant women who visited the Federal Medical Center, Umuahia, from January to February 2023. A self-administered questionnaire was answered by conveniently sampled participants. Data were collected about their sociodemographic characteristics, knowledge, attitude, and practice. Descriptive statistics and inferential statistics utilizing the Pearson's chi-Square test were used for data analysis. The level of significance was set at p < 0.05. Results: One hundred and fifty-two pregnant women completed the questionnaire (60.8% response rate) and were mostly married (n = 148; 95.0%). Majority were between the age of 25 to 35 years (n = 107; 70.4%), had a university/bachelor's degree (n = 94; 61.8%), and were business women (n = 85; 56.0%). About 35.5% of the respondents had good knowledge of medication restrictions in pregnancy. The majority of the respondents had a positive attitude (n = 98; 64.5%) and good practice (n = 139; 91.4%). Conclusion: The findings established that a substantial proportion of the women had a positive attitude and good practice of medication use and restrictions in pregnancy. However, the level of knowledge was surprisingly poor among the study group. There is a need to educate pregnant women on safe medication use and avoidance during pregnancy.